Patterns of antituberculous drug resistance in Eastern Saudi Arabia: A 7-year surveillance study from 1/2003 to 6/2010 - Liaqat Ali Chaudhry; Nagamani Rambhala; Ali Saad Al-Shammri; Jaffar A. Al-Tawfiq (Springer, 2019)
Objective: To examine the patterns of antituberculous drug resistance of Mycobacterium tuberculosis in patients with pulmonary and extra-pulmonary tuberculosis in the Eastern province of the Kingdom of Saudi Arabia. Methods: This is a retrospective study of antibiotic susceptibility of 1681 non-repetitive M. tuberculosis isolates from 1/2003 to 6/2010. Results: Of the total patients, 41% (n = 687) were Saudis and 59% (n = 994) were non-Saudis. The pulmonary and extra-pulmonary specimens constituted 68% (n = 1148) and 32% (n = 533), respectively. The incidence of resistance was 15.5% to one or more of anti-tuberculosis drugs. The resistance rates to first-line drugs were as follows: streptomycin (10.4%), INH (9.8%), rifampicin (1.5%) and ethambutol (1.0%). Multi-drug resistant tuberculosis was present in 1.4% (n = 24) of the sample. Conclusion: INH resistance in this study was relatively high, whereas the rate of MDR-TB was low. A rate of MDR-TB observed in this study was 1.4%. Thus, an empiric four-drug therapy is required to treat patients with tuberculosis in this area of Saudi Arabia.